2022
DOI: 10.3389/fpubh.2022.969251
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis and mortality predictors of COVID-19 in a pediatric cohort in Mexico

Abstract: BackgroundThe new coronavirus SARS-CoV-2 pandemic has been relatively less lethal in children; however, poor prognosis and mortality has been associated with factors such as access to health services. Mexico remained on the list of the ten countries with the highest case fatality rate (CFR) in adults. It is of interest to know the behavior of COVID-19 in the pediatric population. The aim of this study was to identify clinical and sociodemographic variables associated with mortality due to COVID-19 in pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…We found that diabetes was associated with hospital admission, invasive mechanical ventilation, and death. Similar results have been recorded in pediatric populations younger than 12 months, and those with comorbidities have a worse prognosis [ 19 , 20 ]. Consistent with other studies, adult patients with diabetes had higher hospital admission rates and a higher risk of dying [ 12 ].…”
Section: Discussionsupporting
confidence: 84%
“…We found that diabetes was associated with hospital admission, invasive mechanical ventilation, and death. Similar results have been recorded in pediatric populations younger than 12 months, and those with comorbidities have a worse prognosis [ 19 , 20 ]. Consistent with other studies, adult patients with diabetes had higher hospital admission rates and a higher risk of dying [ 12 ].…”
Section: Discussionsupporting
confidence: 84%
“…Numerous studies have demonstrated that COVID‐19 patients who also have conditions like hypertension, diabetes, and obesity typically experience worse outcomes 55,57,58 . The body's capacity to mount an immune response against viral infections can be hindered by these comorbidities, which can disrupt the immune system's normal function 59,60 …”
Section: Discussionmentioning
confidence: 99%
“… 55 , 57 , 58 The body's capacity to mount an immune response against viral infections can be hindered by these comorbidities, which can disrupt the immune system's normal function. 59 , 60 …”
Section: Discussionmentioning
confidence: 99%